High resolution study of the lowest inversion-vibration bands of 15NHD2: Interacting bands ν5/ν6/2ν2; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 250 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Gromova O. V. Olga Vasilievna; Fomchenko A. L. Anna Leonidovna; Tchana F. K. Fridolin Kwabia (2020, 2020)
Title screen